Analisis Regresi Pada Pengaruh PDRB Menurut Lapangan Usaha Terhadap Pertumbuhan Ekonomi Di Kabupaten Tapanuli Selatan - Novita Aswan; Yusra Fadhillah; Aris Munandar Harahap (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
This study aims to analyze the relationship between the Gross Domestic Product (GDP) based on economic sectors and the economic growth rate in South Tapanuli Regency. Secondary data on GDP in South Tapanuli Regency categorized by economic sectors, compiled by the Central Bureau of Statistics (BPS), were used for the analysis. The selected sectors were those contributing more than 5% to the GDP by economic sectors. Additionally, data on the percentage of regional economic growth in South Tapanuli Regency from 2011 to 2021 were incorporated.The analysis results indicate that all five variables collectively have a significant influence on economic growth (0,042 < 0.05) with a correlation rate of 84.2%. Specifically, the manufacturing industry sector demonstrates a positive and significant impact on economic growth. On the other hand, the agriculture, forestry, and fisheries sector; mining and quarrying sector; construction sector; and trade, repair of motor vehicles, and motorcycles sector show positive contributions but are not statistically significant. This research provides valuable insights for the local government in understanding the role of GDP in determining economic growth. The findings can serve as a foundation for formulating policies and economic development strategies in South Tapanuli Regency, aiming to achieve sustainable and high-quality economic growth.